2007
DOI: 10.1007/s11571-007-9028-7
|View full text |Cite
|
Sign up to set email alerts
|

A neural network model of attention-modulated neurodynamics

Abstract: Visual attention appears to modulate cortical neurodynamics and synchronization through various cholinergic mechanisms. In order to study these mechanisms, we have developed a neural network model of visual cortex area V4, based on psychophysical, anatomical and physiological data. With this model, we want to link selective visual information processing to neural circuits within V4, bottom-up sensory input pathways, top-down attention input pathways, and to cholinergic modulation from the prefrontal lobe. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Furthermore, two mechanisms, namely: bottom-up and top-down, control spatial attention. In summary, bottom-up processing is driven by focusing on properties of the stimulus, especially its salient properties while top-down mechanism is goal driven and is under the control of the subject attending to the task (Shipp 2004;Gu and Liljenström 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, two mechanisms, namely: bottom-up and top-down, control spatial attention. In summary, bottom-up processing is driven by focusing on properties of the stimulus, especially its salient properties while top-down mechanism is goal driven and is under the control of the subject attending to the task (Shipp 2004;Gu and Liljenström 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As an effect of the attention mechanism, neural responses are modulated by attention in specific regions of brain (Carrasco 2011;Bisley 2011;Gu and Liljenström 2007;Treue and Maunsell 1999;Sundberg et al 2009;Seidemann and Newsome 1999;Herrington and Assad 2009;Martinez-Trujillo and Treue 2004). Previous studies have shown that in different brain regions, an increase in neural response occurs when attention focuses on a stimulus that falls within a cell's receptive field (RF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the visual attention (Desimone and Duncan 1995;Gu and Liljenstrom 2007;Haab et al 2011) has been widely used in pattern recognition field and received good results in natural images. Visual attention is one of the most important parts of consciousness Koch 1998, 2003;Crick et al 2004), with the aid of which human vision can easily and rapidly focus on salient objects in his sight but machines cannot.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a visual mechanism referred to as attention selection has evolved, which rapidly shifts across the scene under view and selects a small area for further cortical processing (Treisman and Gelade 1980;Koch and Ullman 1985;Desimone and Duncan 1995;Crick and Koch 1998;Bundesen and Habekost 2008;Gu and Liljenstrom 2007;Haab et al 2011). Typically, attention selection is either driven in bottom-up manner or controlled by top-down cues (Itti and Koch 2001;Treisman and Gelade 1980;Koch and Ullman 1985).…”
Section: Introductionmentioning
confidence: 99%